Genetic subtraction profiling identifies genes essential for Arabidopsis reproduction and reveals interaction between the female ganetophyte and the maternal sporophyte - Johnston, A.J. (2007)
The embryo sac contains the haploid maternal cell types necessary for double fertilization and subsequent seed development in plants. Large-scale identification of genes expressed in the embryo sac remains cumbersome because of its inherent microscopic and inaccessible nature. We used genetic subtraction and comparative profiling by microarray between the Arabidopsis thaliana wild-type and a sporophytic mutant lacking an embryo sac in order to identify embryo sac expressed genes in this model organism. The influences of the embryo sac on the surrounding sporophytic tissues were previously thought to be negligible or nonexistent; we investigated the extent of these interactions by transcriptome analysis.